QUANTITATIVE CHANGES OF FUNCTIONAL AND SPEED ABILITIES OF WATER POLO PLAYERS IN PREPARATION AND COMPETITION PERIOD - Ivan Janković; Marko Aleksandrović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The main objective of this research is to establish quantitative changes of speed and functional abilities of cadet water polo players in preparation and competition period. The sample of examinees consisted of 50 water polo players aged 14-15, with water polo experience of at least two years, attendants of five clubs of Central and South East Serbia. The sample of 14 variables is used for speed and functional abilities (7 variables each) during three mounts training treatment. Results processed by canonical discrimative analysis present quantitative differences in speed and functional abilities space based on applicated manifestations.